Toxicidade aguda e efeitos histopatológicos do herbicida diquat na brânquia e no fígado da tilápia nilótica (Oreochromis niloticus) - Peixoto Henares, Matheus Nicolino; da Cruz, Claudinei; Gomes, Gabriela Roncada; Pitelli, Robinson Antonio; Fernandes Machado, Marcia Rita (Universidade Estadual de Maringa, 2008)
The lethal concentration of 50% (LC (I) and the histopathologic effects of diquat herbicide on Nile tilapia (Oreochromis niloticus) fish were evaluated in three experiments. The fishes were exposed to concentrations of 0, 25, 30, 35, 40, 45, 50, 55 and 60 rug diquat L-1, and gill and liver histology were evaluated in the surviving fishes. The estimated LC (I) (50-96h) of diquat was 37.28 mg L-1, with lower limits of 33.12 mg L-1 and upper limits of 41.44 mg L-1. In the treatment with 30, 35 and 40 mg L-1, signs of apical fusion of the secondary lamellae were observed; with 45 and 50 mg L-1, congestion of the primary lamellae was observed; in the treatment with 55 mg L-1, congestion of blood vessels on secondary lamellae took place. The livers of fishes in treatments with 0, 25, 30 and 35 mg L-1showed cordonal organization of hepatocytes. In the treatments with 40 and 45 mg L-1, hypertrophy of hepatocytes took place; with 50 and 55 mg L-1, cell fusion and the presence of vacuoles inside hepatocytes were observed. Diquat presented low risk of toxicity for nile tilapia, as the more severe histopathologic alterations occurred only in higher concentrations.
Acute toxicity and histopathologic effects of diquat herbicide on the gill and liver of Nile tilapia (Oreochromis niloticus).